2018
DOI: 10.1002/smj.2716
|View full text |Cite
|
Sign up to set email alerts
|

Undervaluation of directors in the board hierarchy: Impact on turnover of directors (and CEOs) in newly public firms

Abstract: Research summary: We examine the consequences of the formalization of the board leadership structure at IPO for board‐level turnover. We introduce the concept of director undervaluation. It indicates the degree to which a director’s qualifications based on normatively accepted criteria for board leadership are not duly reflected in his/her appointments to the board chair and committee chair positions. We find that the higher the average undervaluation of directors on the board (“board undervaluation”), the gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 118 publications
(183 reference statements)
2
49
0
2
Order By: Relevance
“…Moreover, one study found that appointing a board chair who was not previously appointed to this role-despite having higher qualifications than other directors-might lead firms to experience a higher rate of director turnover, followed by the recruitment of less qualified new board members (Garg et al, 2019). To curb a high director turnover and the development of a negative board climate, board members may be more vigilant in their evaluation and monitoring roles (Garg, Li, & Shaw, 2018). (Aktas et al, 2019;Kim et al, 2009; cf.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one study found that appointing a board chair who was not previously appointed to this role-despite having higher qualifications than other directors-might lead firms to experience a higher rate of director turnover, followed by the recruitment of less qualified new board members (Garg et al, 2019). To curb a high director turnover and the development of a negative board climate, board members may be more vigilant in their evaluation and monitoring roles (Garg, Li, & Shaw, 2018). (Aktas et al, 2019;Kim et al, 2009; cf.…”
Section: Discussionmentioning
confidence: 99%
“…This limited mobility as employees had fewer external contacts and thus less information about external career opportunities. Garg, Li, and Shaw (2018) found that the frequency of social interactions among board members increased the likelihood of turnover for those directors who were under-evaluated (i.e., not appointed as a board chair or a committee chair despite their qualifications). Garg et al argued that as social interactions among board members increase, such interactions remind under-evaluated directors of the unjustified assessment, increasing rumination about the injustice and leaving behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sample includes data for each firm beginning with the first year as a publicly traded firm. Following Garg et al (2018), IPO year is coded as 1 if a firm went public in a given year and 0 otherwise. This control captures the potential vulnerability of firm performance to its newly public status.…”
Section: Methodsologymentioning
confidence: 99%